Fraction Algebra Problem

Jason76

Senior Member
Joined
Oct 19, 2012
Messages
1,180
\(\displaystyle \dfrac{3}{4} t^{-1/4} = \dfrac{1}{4} t^{-1/3}\) hint?
 
\(\displaystyle \dfrac{\dfrac{3}{4}t^{-1/4}}{t^{-1/4}} = \dfrac{\dfrac{1}{4}t^{-1/3}}{t^{-1/4}}\)


\(\displaystyle \dfrac{3}{4} = \dfrac{1}{4}t^{-1/12}\) :confused:

\(\displaystyle \dfrac{12}{4} = t^{-1/12}\) :confused:


\(\displaystyle \dfrac{3}{1} = t^{-1/12}\) :confused: Next move?
 
Last edited:
\(\displaystyle \dfrac{\dfrac{3}{4}t^{-1/4}}{t^{-1/4}} = \dfrac{\dfrac{1}{4}t^{-1/3}}{t^{-1/4}}\)


\(\displaystyle \dfrac{3}{4} = \dfrac{1}{4}t^{-1/12}\) :confused:

\(\displaystyle \dfrac{12}{4} = t^{-1/12}\) :confused:


\(\displaystyle \dfrac{3}{1} = t^{-1/12}\) :confused: Next move?

t1/12 = 1/3 ..... now your move...
 
Top